2021
DOI: 10.7903/cmr.20647
|View full text |Cite
|
Sign up to set email alerts
|

Music streaming characteristics and emotional consumption as determinants of consumer satisfactions and intention to purchase

Abstract: The present study analyzes consumers perceptions of music streaming and how such perceptions might influence customers brand loyalty and purchase intent. The competitive advantages of music streaming, widely known for its cost-saving measures, ease of use, and worldwide accessibility, are carefully reviewed herein. The S-O-R Theory commonly employed in psychology studies is applied in this study to explain the relationship between the product characteristics of streaming music (e.g., price, content quality, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 90 publications
(146 reference statements)
0
12
0
Order By: Relevance
“…background music) can generate both positive and negative emotions. Previous study found that only positive emotions will affect purchase intention (Hsu et al, 2021). Similarly, product offerings and price are not the predictor of satisfaction because too many products offered with different price tags might create confusion to customers.…”
Section: Data Analysis and Findingsmentioning
confidence: 93%
“…background music) can generate both positive and negative emotions. Previous study found that only positive emotions will affect purchase intention (Hsu et al, 2021). Similarly, product offerings and price are not the predictor of satisfaction because too many products offered with different price tags might create confusion to customers.…”
Section: Data Analysis and Findingsmentioning
confidence: 93%
“…Regarding music streaming services, satisfaction is the evaluative belief that customers have the choice to use and buy music being streamed on websites or apps they consider reputable, they deem the right choice, and where they believe that the service provided fulfills their needs (Cronin et al, 2000;Khatib et al, 2019). Based on previous literature, in streaming services, positive emotions, and customer engagement can influence consumers' satisfaction levels (Gupta and Singharia, 2021;Hsu et al, 2021). Also, Khatib et al (2019) revealed that reliability and responsiveness, expressed as performance were significant to satisfaction (Khatib et al, 2019).…”
Section: Satisfactionmentioning
confidence: 98%
“…On the other hand, QSE impacts users' intentions to keep and order streaming services in the future, however, the association between satisfaction and intentions to keep and order streaming services weakens with habit strength (Gupta and Singharia, 2021). Therefore, some researchers have studied the influence of consumers' satisfaction on loyalty (or willingness to continue to subscribe) in the streaming services domain (Kondo et al, 2010;Khatib et al, 2019;Hsu et al, 2021). The user behavior-satisfaction-loyalty model is established to explain the trajectory of influence on loyalty and repurchase intention (from satisfaction to intention to continued future use) (Kondo et al, 2010) and can be predicted by consumer satisfaction (Khatib et al, 2019;Hsu et al, 2021).…”
Section: Qsementioning
confidence: 99%
See 2 more Smart Citations